A diverse global fungal library for drug discovery - Niu, Guodong; Annamalai, Thirunavukkarasu; Wang, Xiaohong; Li, Sheng; Munga, Stephen; Niu, Guomin; Tse-Dinh, Yuk-Ching; Li, Jun (PeerJ, 2020)
Background Secondary fungal metabolites are important sources for new drugs against infectious diseases and cancers. Methods To obtain a library with enough diversity, we collected about 2,395 soil samples and 2,324 plant samples from 36 regions in Africa, Asia, and North America. The collection areas covered various climate zones in the world. We examined the usability of the global fungal extract library (GFEL) against parasitic malaria transmission, Gram-positive and negative bacterial pathogens, and leukemia cells. Results Nearly ten thousand fungal strains were isolated. Sequences of nuclear ribosomal internal transcribed spacer (ITS) from 40 randomly selected strains showed that over 80% were unique. Screening GFEL, we found that the fungal extract from Penicillium thomii was able to block Plasmodium falciparum transmission to Anopheles gambiae, and the fungal extract from Tolypocladium album was able to kill myelogenous leukemia cell line K562. We also identified a set of candidate fungal extracts against bacterial pathogens.
Keywords: Fungus; Secondary metabolites; Small molecule; Natural product; Drugs; Anti-malaria; Antibiotics; Anti-leukemia